Investigating the Interpersonal Intelligence of Social Science Educators using a Phenomenological Methodology in Primary Education - Marianus Tapung (Jurnal Syntax Transformation, 2025)
Interpersonal intelligence is an important component in the teaching profession that enables them to understand and build effective relationships with students. This study aims to explore the interpersonal intelligence of social education teachers in primary schools in the Manggarai region, which has unique social and cultural characteristics. This study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews and classroom observations of twelve social education teachers who have a minimum of five years of teaching experience. Data analysis was conducted using a thematic approach and triangulation of methods to ensure the validity of the findings. The findings show that teachers have a diverse understanding of interpersonal intelligence, which is mostly formed through teaching experience. Teachers successfully implement various learning strategies that integrate local wisdom values, but also face challenges such as limited time and resources. This research confirms the importance of interpersonal intelligence in improving the effectiveness of social education learning in primary schools. The results of this study provide a basis for developing strategies to improve teachers' interpersonal competencies as well as education policies that are more responsive to local needs in Manggarai.